Internalisasi Nilai-Nilai Pelajar Rahmatan Lil Alamin dalam Mata Pelajaran Akidah Akhlak di MTsN 5 Blitar - Anggraini, Mentari Cahya Dwi; Asrori, Mohammad; Yahya, Mokhammad (Akhlaqul Karimah: Jurnal Pendidikan Agama Islam, 2025)
Education plays a fundamental role in shaping students' character and competencies to face global challenges in the Industrial Revolution 4.0 and Society 5.0 eras.  This study aims to analyze the implementation of the Rahmatan Lil Alamin project module in Akidah Akhlak learning at MTsN 5 Blitar and evaluate its impact on students' character development. The background of this research is based on the importance of character education rooted in Islamic values in addressing the challenges of globalization, particularly in overcoming the decline in students' character index due to the lack of an applicative approach in religious education.This research employs a qualitative approach with a case study method. Data were collected through observations, interviews, and documentation, involving teachers, students, and school management as primary sources. The findings indicate that the internalization of Rahmatan Lil Alamin values is carried out through a module design that balances cognitive, affective, and psychomotor aspects. Implementation is conducted in a block system after the mid-term exam and through a co-curricular approach that connects learning with religious activities and social projects.The analysis results show an improvement in students' character, particularly in aspects of compassion, tolerance, and social awareness. However, several challenges remain, such as differences in students' levels of understanding and the influence of external environments. This study is expected to provide recommendations for educators and policymakers to enhance the effectiveness of Islamic values-based education in madrasahs.